(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2019)
The work one carries out in the nursery of Cienaguilla belonging of the Managerial Unit of Base Silvícola Campechuela (UEB) with the objective of avoiding the attack of the "Damping off "in the cultivation of the Acacia mangiun Will in the nursery stage and to evaluate the survival in the plantation and their development in different located of plantation. The assembly leaned on totally at random in a design of blocks with three replicas. They were evaluated the effectiveness of three treatments applied pregerminatives. In this state of life the attributes and morphological and physiologic indexes were evaluated that is: diameter of neck of the root, height, relationship PA/PR, index slenderness of Dickson, percentage of fine and thick roots. In the plantation stage it evaluated it to him the survival and the development of the different parameter dasometrics in different plantation places.